Nematicidal activity of Trichoderma harzianum-derived secondary metabolites against Meloidogyne incognita and metabolomic profiling of selected potent isolates (Asian Journal of Agriculture, 2025)
Abstract. Pradana AP, Sholehah S, Andriyani DR, Hoesain M, Astuti W, Hadiani RU, Masnilah R, Adiwena M, Putri D. 2025. Nematicidal activity of Trichoderma harzianum-derived secondary metabolites against Meloidogyne incognita and metabolomic profiling of selected potent isolates. Asian J Agric 9: 326-338. Root-knot nematodes, especially Meloidogyne incognita, reduce global crop yields, necessitating the development of safe and effective management approaches. While chemical nematicides can mitigate infestations, they often present environmental concerns and potentially foster resistance in target nematodes. Consequently, using antagonistic fungi, particularly Trichoderma harzianum, has gained traction as an eco-friendly solution. Nonetheless, the viability of T. harzianum under field conditions is often compromised by abiotic and biotic factors. This study investigated the nematicidal efficacy and secondary metabolite composition of four T. harzianum isolates (AJG, TGL, SBS, and SKS) collected from distinct geographical regions. In vitro assays revealed that the AJG and TGL isolates elicited the most potent effects, achieving >75% egg-hatching inhibition and >93% juvenile mortality at 168 hours post-treatment. Gas chromatography-mass spectrometry indicated that fatty acid esters, including methyl palmitate and methyl oleate, were the major contributors to nematicidal effects through membrane disruption. Notable differences in metabolite profiles between isolates highlight isolate-specific biochemical pathways impacting suppressive capacity. The predominance of fatty acids underscores their critical function in controlling nematodes, offering prospects for developing stable, environmentally friendly formulations. These results underscore the potential of T. harzianum-derived metabolites for integrated nematode management. They also emphasize the importance of isolate selection and metabolite profiling in designing targeted, sustainable strategies to combat root-knot nematodes, empowering the audience with this crucial knowledge.
Keywords: Biological control, fatty acid esters, GC-MS analysis, ovicidal activity, root-knot nematode